2017
DOI: 10.1515/geochr-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of climatic changes during interpleniglacial in the geoecosystems of South-Eastern Poland

Abstract: About 70% of the last cold stage was taken by transitional phases of continuous fluctuations of climate and permafrost extension. All this is reflected especially well in slope types and the thickness of slope, fluvial and aeolian deposits. Very distinct and relatively fast changes took place around 33-30 ka BP: the aridification of climate with an ice sheet transgression, expansion of continuous permafrost and the onset of loess deposition. The greatest transformations of slopes and river valleys in the Carpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…To wards the north, the Ho lo cene floodplain is re stricted by a ter race with Pleis to cene loess at its sur face, 2-3 km in width and with a height of up to 20 m above the mean river level in the Wis³a River val ley in the re search area (Mamakowa and OErodoñ, 1977;Gêbica, 2004;Wójcik and Lewandowski, 2010;Starkel et al, 2017). Land slides are lo cally as so ci ated with the es carp ments of this ter race (Wójcik, 2015a, b).…”
Section: Research Areamentioning
confidence: 99%
“…To wards the north, the Ho lo cene floodplain is re stricted by a ter race with Pleis to cene loess at its sur face, 2-3 km in width and with a height of up to 20 m above the mean river level in the Wis³a River val ley in the re search area (Mamakowa and OErodoñ, 1977;Gêbica, 2004;Wójcik and Lewandowski, 2010;Starkel et al, 2017). Land slides are lo cally as so ci ated with the es carp ments of this ter race (Wójcik, 2015a, b).…”
Section: Research Areamentioning
confidence: 99%
“…In the selection process, we were guided by their regular functioning and the specificity of the reactions of each of them to changes in climatic conditions. Some sites and group of sites had already been analyzed by the authors: one site in the Sudeten Foreland (Krzyszkowski et al 1995(Krzyszkowski et al , 1999(Krzyszkowski et al , 2001, numerous sites from the Subcarpathian Basins (Gębica et al 2015;Starkel et al 2017), the Holy Cross Mountains in the highlands of southern Poland (Ludwikowska-Kędzia 2018), and the lowlands of central Poland (Rotnicki 1987;Krzyszkowski 1990Krzyszkowski , 1991Kasse et al 1998;Petera 2002;Krzyszkowski and Kuszell 2007;Wachecka-Kotkowska et al 2014, 2018Dzieduszy ńska 2019). However, no collective analysis of this data has ever been made.…”
Section: Research Areamentioning
confidence: 99%
“…Therefore, it seems that such environments could register the same cycles of warming and cooling as those recorded in ice cores for the earlier period of MIS 3-2. It should be noted that previous studies for the Subcarpathian Basins (Gębica et al 2015;Starkel et al 2017), for which we have numerous investigated sites and dates, as well as research in the Holy Cross Mountains (Ludwikowska-Kędzia 2000, 2018, showed that collective reconstructions (including analyses of summed probability density distributions of radiocarbon and luminescence dates) can help to identify warming-cooling periods during the Interpleniglacial.…”
Section: Introductionmentioning
confidence: 99%
“…Jary, 2007) stratigraphic position of the Komorniki interstadial soils (Jersak et al, 1992) and Gi/ LMd and Gi/LMs (Maruszczak, 1991b) seem to fit well in the unstable climate period of MIS 3 in southern Poland. It was a period of multiple climatic changes (cooling and warming phases), alternation of periods of landscape stabilisation, and activity of periglacial loess sedimentation and/or slope processes (Starkel et al, 2017). The soil unit formed at that time was formed as a single horizon (long-term developing) or as a set of soil subunits, usually two, overlapping or separated layers by loess, e.g.…”
Section: Loess Stratigraphymentioning
confidence: 99%
“…Loess sites are grouped in the southern part of the country, marking the periglacial zone of the Weichselian glaciation (named Vistulian in Poland). These areas, as a zone of the far foreland of the continental ice sheet, constituted a specific transition zone between different climatic-landscape periglacial areas with a characteristic 'migrating' mosaic of different habitats of tundra, forest-tundra, steppe, forest-steppe, and forest of variable areas (Starkel, 1977;1988;Starkel et al, 2017;Łanczont et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%